2016
DOI: 10.18632/oncotarget.12107
|View full text |Cite
|
Sign up to set email alerts
|

c-Cbl mediates the degradation of tumorigenic nuclear β-catenin contributing to the heterogeneity in Wnt activity in colorectal tumors

Abstract: Despite the loss of Adenomatous Polyposis Coli (APC) in a majority of colorectal cancers (CRC), not all CRCs bear hallmarks of Wnt activation, such as nuclear β-catenin. This underscores the presence of other Wnt regulators that are important to define, given the pathogenic and prognostic roles of nuclear β-catenin in human CRC. Herein, we investigated the effect of Casitas B-lineage lymphoma (c-Cbl) on nuclear β-catenin, which is an oncoprotein upregulated in CRC due to loss-of-function APC or gain-of-functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…2, A, C, and E), we posited an inverse relationship between STUB1 and TF in the uremic milieu. However, the precise demonstration of a relationship between proteins requires their quantification, which is challenging in heterogeneous human tissues using conventional methods (31). Therefore, we developed an object-level intensity estimation algorithm to quantify TF and STUB1 expressions.…”
Section: Resultsmentioning
confidence: 99%
“…2, A, C, and E), we posited an inverse relationship between STUB1 and TF in the uremic milieu. However, the precise demonstration of a relationship between proteins requires their quantification, which is challenging in heterogeneous human tissues using conventional methods (31). Therefore, we developed an object-level intensity estimation algorithm to quantify TF and STUB1 expressions.…”
Section: Resultsmentioning
confidence: 99%
“…We found that although response to first line chemotherapy was a strong and independent predictor of overall survival, Black patients still had poorer survival despite a lack of difference in the response to therapy, comorbidities, BMI or tumor burden at the time of presentation. While our study does not rule out the possibility of molecular differences (i.e., RAS mutation, BRAF mutation, and MSI status), it raises a possibility of other pathogenic factors that may contribute to racial differences [49]. More real-world studies are needed to address in depth the influence of race on CRC progression and survival.…”
Section: 5 Conclusionmentioning
confidence: 99%
“…[26][27][28] To further uncover the underlying mechanisms of the suppression of RCC cell growth and migration mediated by miR-200a-3p, we searched for miRNA targets and identified CBL as a novel target of miR-200a-3p. 30 High CBL expression has actually been recognized as linked with the development of several types of cancer, including gliomas, gastric carcinoma, colorectal cancer, prostate cancer, breast cancer and non-small-cell lung cancer. 29 For example, CBL generally targets receptor tyrosine kinases and other nonreceptor tyrosine kinases, such as Src family kinases, and mutations in the components of this pathway may result in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%